Effects of welding speed on welding process stability, microstructure and mechanical performance of SUS304 welded by local dry underwater pulsed MIG. (24th February 2023) - Liao, Haipeng; Zhang, Wenxu; Xie, Huimin; Li, Xuyan; Zhang, Qin; Wu, Xiangmiao; Tian, Jiyu; Wang, Zhenmin
Abstract: To reveal the effects of welding speed on welding process stability, microstructure, and mechanical performance of SUS304 weldments fabricated by local dry underwater pulsed metal inert-gas welding (LDU-PMIG), the electrical signals and droplet transfer behaviours of welding process, phase morphologies and distributions, grain sizes and grain boundary characteristics, microhardness, and tensile strength of these weldments were investigated in this work. The results indicated that with the increase of welding speed from 9.0 mm/s to 16.2 mm/s, the welding process stability first improved and then deteriorated. The more rapid water cooling rate caused by the increase of welding speed led to the δ-ferrite morphological evolution from skeletal to lath, which promoted the transformation from brittleness to ductility in the weld mechanical performance. Furthermore, the proportions of small-size grains (less than 10 μm) and low-angle grain boundaries (2–15°) first increased and then decreased, which determined the same variation trend in the comprehensive mechanical performance of weldments. The weldment obtained at 12.6 mm/s exhibited the highest microhardness, tensile strength and elongation, which achieved 70.0 %, 92.3 %, and 61.6 % of base metal. These results are conducive to enhance the SUS304 LDU-PMIG weldment quality and facilitate its application in marine equipment field.